Réponses

2014-04-24T22:41:04+02:00
J = (1/8 - 7/12) : ( 7/6 + 7/16)
J = (1 x 3 / 8 x 3 - 7 x 2 / 12 x 2) : (7 x 16 / 6 x 16 + 7 x 6 / 16 x 6)
J = (3/24 - 14/24) : (112/96 + 42/96)
J = -11/24 : 154/96
J = -11/24 x 96/154
J = -1056/3696
J = 528 x 2 / 528 x 7
J = 2/7

K = 1/8 - 7/12 : 7/6 + 7/12
K = 1/8 - 7/12 x 6/7 + 7/12
K = 1/8 - 42/84 + 7/12
K = 1 x 84 / 8 x 84 - 42 x 8 / 84 x 8 + 7 x 56 / 12 x 56
K = 84/672 - 336/672 + 392/672
K = 140/672
K = 28 x 5 / 28 x 24
K = 5/24

L = (1/8 + 7/12) * (6/5 : 4/15)
L = (1 x 3 / 8 x 3 - 7 x 2 / 12 x 2) x (6/5 x 15/4)
L = (3/24 - 14/24) x (90/20)
L = -11/24 x 90/20
L = - 990/480
L = 30 x 33 / 30 x 16
L = 33/16

N = 5/3 - 7/9

     1/4 - 1/2
N = 5 x 3 / 3 x 3 - 7/9
     1/4 - 1 x 2 / 2 x 2
N = 15/9 - 7/9
       1/4 - 2/4
N = 8/9 : -1/4
N = 8/9 x - 4/1
N = -32/9